Modelling foundations and applications 7th European Conference, ECMFA 2011, Birmingham, UK, June 6 - 9, 2011 Proceedings - France, Robert B.; Kuester, Jochen M.; Bordbar, Behzad; Paige, Richard F. (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 7th European Conference on Modelling Foundations and Applications, held in Birmingham, UK, in June 2011. The 19 revised full foundations track papers and 5 revised full applications track papers presented were carefully reviewed and selected from 61 submissions; also included are 5 workshop summaries and abstracts of 4 tutorials. The papers are organized in topical sections on model execution, model analysis, methodology, model management, model transformation, variability analysis and ADLs, and domain-specific modeling.